The Arduino e-kit as Applied in Engineering, Science and Technology e-learning - Oteri, Omae Malack (2020 Sixth International Conference on e-Learning (econf), 2020)
Many technical courses mainly in engineering, science and technology, have always been taught using very expensive equipment usually stationed in a particular lab setup in the university with students accessing these labs in groups. The problem is even compounded further in the case where the number of students is high in a class. This paper discusses the use of an e-kit, which is an Arduino based virtual lab kit, to undertake simulation practicals in the fields of engineering, science and technology a case study of digital electronics, digital practicum and hardware & software practicum that are done by students in these fields. The study involved the development of virtual Arduino based labs using the Autodesk Tinkercad circuits web-based simulator. For full implementation, a laptop or desktop computer with internet access are also required. The first group of students, who were requested to do an evaluation of the kit at the end of the semester, was undertaking computer science. The results were quite positive where the majority of the students indicated that the kit could be introduced in all the other related subjects to make them more enjoyable and easier to understand.